Nanoparticle Delivery of CRISPR/Cas9 for Genome Editing - Duan, Li; Ouyang, Kan; Xu, Xiao; Xu, Limei; Wen, Caining; Zhou, Xiaoying; Qin, Zhuan; Xu, Zhiyi; Sun, Wei; Liang, Yujie (Frontiers in Genetics, 2021)
The emerging clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated system (Cas) gene-editing system represents a promising tool for genome manipulation. However, its low intracellular delivery efficiency severely compromises its use and potency for clinical applications. Nanocarriers such as liposomes, polymers, and inorganic nanoparticles have shown great potential for gene delivery. The remarkable development of nanoparticles as non-viral carriers for the delivery of the CRISPR/Cas9 system has shown great promise for therapeutic applications. In this review, we briefly summarize the delivery components of the CRISPR/Cas9 system and report on the progress of nano-system development for CRISPR/Cas9 delivery. We also compare the advantages of various nano-delivery systems and their applications to deliver CRISPR/Cas9 for disease treatment. Nano-delivery systems can be modified to fulfil the tasks of targeting cells or tissues. We primarily emphasize the novel exosome-based CRISPR/Cas9 delivery system. Overall, we review the challenges, development trends, and application prospects of nanoparticle-based technology for CRISPR/Cas9 delivery.